Kakuma Is Not Swahili for “Nowhere”: Narratives of the Host Community and the Meaning of a False Translation - Shadle, Brett (Refuge, 2026)
This article examines the widely used but false claim that the word Kakuma, which is the site of a large refugee camp, means “nowhere” in Swahili. It traces the origin and spread of this false translation and how Kakuma has in fact long been “somewhere” for the Turkana people. “Nowhere” makes sense only by comparing Kakuma to “somewhere,” which in turn draws on long-standing hierarchies of traditional/modern or underdeveloped/developed. Thus, through the “nowhere” narrative, the region and Turkana people are consigned to pre-modernity. This study argues for a better understanding of from where narratives by and about refugees and host communities emerge, why they come to be accepted, and the impacts they might have.